Quantifying errors in wind and wave measurements from a compact, low-cost wave buoy - Beckman, Jesse N.; Long, Joseph W. (Frontiers in Marine Science, 2022)
A yearlong wind and wave dataset derived from a cost-effective GPS wave buoy (Spotter) is compared to waves obtained from an accelerometer wave buoy (Datawell) and winds obtained from a collocated meteorological buoy. Overall, there was a strong correlation in bulk wave parameters obtained from the Spotter buoy and the Datawell buoy (RMSE of 0.06 m, 0.27 s, and 21.89° for significant wave height, mean wave period, and peak wave direction, respectively). Similarly, the bulk characteristics compared well when separating the directional wave spectra into sea and swell components with more scatter in mean wave periods for lower frequencies. Measurements of mean directional spread from the Spotter buoy were 7.51° larger than the Datawell, spreading more wave energy across different directions outside the peak direction. Additional analysis indicates that the increased directional spreading arises from a bias in the a1 and b1 spectral moments. Using the equilibrium frequency range of the wave energy spectrum, the Spotter buoy can derive wind speed and direction. This study found the Spotter buoy can report wind speed and direction with reasonable accuracy but underestimates wind speeds less than 4 m/s and greater than 8 m/s and was less accurate reporting wind directions oriented offshore. A comparison with a Spotter buoy in deeper water revealed the Spotter buoy further offshore was most accurate in reporting wind directions indicating this proxy-based measurement of wind speed and wind direction may be significantly influenced by fetch and local geography (e.g., large-scale cuspate coastlines).